AB0615 Is Increased Serum Interleukin-35 Levels A Disease Activity Marker in Dermatomyositis and Polymyositis?. (15th July 2016) - Yin, L.; Wang, G.; Ge, Y.
Abstract : Background: Idiopathic inflammatory myopathies (IIMs) are a group of heterogeneous, systemic disorders [1].DM and PM are two main clinical subtypes of IIMs in Chinese population. The pathogenesis underlying myositis is complicated and yet not well clarified. In IIM, cytokines are secreted by immune cells, endothelial cells and muscle cells, and can exert pro-inflammatory or anti-inflammatory effects [2–3].Interleukin-35 (IL-35) is a heterodimeric cytokine composed of two subunits, p35 and EBI3 [4].To date, IL-35 has been studied in several kinds of autoimmune disease but its role remains controversial under the pathology conditions. Therefore, we measure IL-35 expression in circulation of IIM patients and to evaluate its association with myositis-related features. Objectives: The purpose of this study was to assess the level of serum IL-35 in indiopathic inflammatory myopathies (IIMs) patients and to evaluate its association with IIM-related features. Methods: Clinical data and serum samples were collected from76 DM, 28 PM and 43 healthy controls. Follow-up of 34 patients was also conducted. Serum IL-35 levels were detected by enzyme linked immunosorbent assay (ELISA). Disease activity of myositis patients was assessed according to the myositis disease activity assessment visual analogue scale (MYOACT). Results: IL-35 serum levels were increased in myositis patients compared to healthy controls (P<0.001). No differences in IL-35 serum levels were found between DM and PM (P=0.468). Serum level of IL-35 with IIM was negatively correlated with disease duration (r =-0.231, P=0.019). Patients with dysphagia had higher IL-35 levels than those without (P=0.001). But, there was no statistically significant difference between IIM patients with interstitial lung disease (ILD) and without (P=0.997). Cross-sectional correlation analysis showed a positive correlation of serum IL-35 with CK (r=0.285, P=0.004), ESR (r=0.235, P=0.02), serum ferritin (SF) (r=0.471, P=0.001), LDH (r=0.401, P<0.001) and MYOACT scores (r=0.227, P=0.021). Serum IL-35 levels were significantly higher in ANA (P=0.026), anti-HMGCR (P=0.038) and anti-SRP (P=0.009) antibody positive patients than that in negative respectively. Follow-up study showed the change of IL-35 levels after treatment correlated with the change of MYOACT scores (r=0.375, P=0.029). Conclusions: Serum IL-35 was elevated in both PM and DM patients and increased serum IL-35 was associated with dysphagia of myositis patients but not ILD. The serum levels of IL-35 also correlated with disease activity. These data suggest the increased serum IL-35 is a marker of disease activity and the risk for esophagus involvement in IIM. Finally, IL-35 may participate in the pathophysiological process of IIM. References: Hak AE d P B, de Bleecker JL, Tak PP, de Visser M, Dermatomyositis and Polymyositis: New Treatment Targets on the Horizon. Neth J Med, 2011. 69(10): p. 410–421. IE L, The Role of Cytokines, Chemokines, and Adhesion Molecules in the Pathogenesis of Idiopathic Inflammatory Myopathies. Curr Rheumatol Rep, 2000. 2(3): p. 216–224. Zong M, Lundberg IE, Pathogenesis, Classification and Treatment of Inflammatory Myopathies. Nat Rev Rheumatol, 2011. 7(5): p. 297–306. Collison LW, Workman CJ, Kuo TT, et al., The Inhibitory Cytokine Il-35 Contributes to Regulatory T-Cell Function. Nature, 2007. 450(7169): p. 566–9. Disclosure of Interest: None declared